Method for measuring bone density through the electrical conductivity calculated by Electrical Impedance Tomography - San-Pablo-Juárez, M. A.; Morales-Sánchez, E.; Ireta-Moreno, F.; Ávalos-Zúñiga, R.; González-Barbosa, J. J. (Revista Mexicana de Ingenieria Biomedica, 2017)
In this paper a method to measure bone density was developed. The method consists in the measurement of electrical conductivity of bone by Electrical Impedance Tomography (EIT). A phantom with simulated data of bone is used, applying currents and recording voltages; then a backprojection reconstruction is used to generate maps with graphic conductivity values. The data obtained were analyzed and was obtained a distribution of electrical conductivity of bone, wich varies according to the bone porosity level in each region. A significant advantage of using this method is that is possible to measure electrical conductivity in several directions of the bone, obtaining an effective conductivity. Therefore it is possible to determine the porosity in the bone with measurements of electrical conductivity using the proposed EIT method, this allows to calculate a numerical value for bone density